Assessment of How Oil Factors and Economic Development Impact on Industrial Employment of the Country: Symmetric Analysis - Ilyashova, Guliya; Abinova, Alfiya; Massakova, Saltanat; Kakizhanova, Tolkyn; Andabayeva, Gulmira (International Journal of Energy Economics and Policy, 2025)
Employment is influenced by elements specific to each sector of the labor market. The authors’ goal was to investigate how employment in the industrial sector—which includes the oil and gas sector—is affected by oil factors. Kazakhstan is particularly vulnerable to global shocks, such as shifts in energy policies, because it is a nation that exports raw materials. This study looks at how important factors affect the Republic of Kazakhstan’s Employment in Industry (EMP). The World Data Bank (WDI) provided the data used in the study, which spans the years 1991-2023. GDP per capita, average annual Brent crude oil price, and crude oil production are the study’s explanatory variables. All statistical validation tests were passed by the study, which employed the autoregressive distributed lag (ARDL) approach. According to the estimation results, the lag variables of oil production volume and GDP per capita have a negative short-term impact on employment growth in the sector, whereas the lag variables of oil price and GDP per capita have a positive one. Long-term employment growth in the sector is positively impacted by the lag variables of oil price and GDP per capita, but negatively by the lag variable of oil volume.